Литературная историософия Б. Л. Пастернака («Доктор Живаго») и Е. Г. Водолазкина («Лавр») - Солдаткіна, Яніна Вікторівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статье рассматриваются особенности русской историософской прозы на примере романов Б. Л. Пастернака «Доктор Живаго» и Е. Г. Водолазкина «Лавр». Эти два произведения сближает их историософская пробле¬матика, основанная на христианском представлении о смысле истории, поисках путей преодоления смерти и человеческой зависимости от времени. В центре этих произведений – герой-врач, наделенный даром исце¬ления, но стремящийся прежде всего к духовному просветлению, к идеалу жертвенной любви к людям. Фи-налы обоих романов символически свидетельствуют о вечной жизни и Божьей милости. The article studies the specifics of Russian historiosophical prose in the novels «Doctor Zhivago» by B. L. Pasternak and «Lavr» by Е. G. Vodolazkin. The two novels are similar in their historiosophical implications based on the Christian philosophy of the meaning of history, pursuit of eternal life and human dependency on the passage of time. The main characters of the novels are Doctors capable to heal others, but whose predominant goal is spiritual awakening, achievement of the sacrificial love for the people. Eternal life and God’s mercy are the underlying themes in finale of both of the novels.
Keywords: историософия; время; онтология; аксиология; роман; сюжет и композиция; идеал